2006
DOI: 10.1038/ng1719
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an instructive mechanism of de novo methylation in cancer cells

Abstract: DNA methylation has a role in the regulation of gene expression during normal mammalian development but can also mediate epigenetic silencing of CpG island genes in cancer and other diseases. Many individual genes (including tumor suppressors) have been shown to undergo de novo methylation in specific tumor types, but the biological logic inherent in this process is not understood. To decipher this mechanism, we have adopted a new approach for detecting CpG island DNA methylation that can be used together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
344
0
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 445 publications
(376 citation statements)
references
References 33 publications
28
344
0
4
Order By: Relevance
“…Based on these results, the methylation frequency of miRNA genes seemed to be at least an order of magnitude higher than the methylation frequency of protein-encoding genes, which has been estimated to be in the range of 1-2%. [32][33][34] In agreement with this notion, COBRA analysis of three CpG island-associated protein-encoding genes (p15, p21, NPM) failed to reveal any evidence for methylation in any of the cell lines analyzed (Fig. 2).…”
Section: An Extended Methylation Analysis Of Human Mirna Genessupporting
confidence: 63%
See 1 more Smart Citation
“…Based on these results, the methylation frequency of miRNA genes seemed to be at least an order of magnitude higher than the methylation frequency of protein-encoding genes, which has been estimated to be in the range of 1-2%. [32][33][34] In agreement with this notion, COBRA analysis of three CpG island-associated protein-encoding genes (p15, p21, NPM) failed to reveal any evidence for methylation in any of the cell lines analyzed (Fig. 2).…”
Section: An Extended Methylation Analysis Of Human Mirna Genessupporting
confidence: 63%
“…The frequency of miRNA gene methylation thus appears to be substantially higher than for protein-encoding genes. [32][33][34] This difference is remarkable because both gene groups seem to be methylated by similar mechanisms, as indicated by their dependency on the cooperative activities of DNMT1 and DNMT3B. 25 It is possible that the susceptibility of miRNA-associated CpG islands for DNA methylation is a consequence of their sequence composition.…”
Section: The Functional Significance Of Mirna Gene Methylationmentioning
confidence: 99%
“…In the mouse genome, the HpaII/MspI sites are concentrated in the region between ‫1מ‬ kb and +1 kb from the TSS. In the case of meDIP, the precipitation efficiency of methylated DNA depended on the density of CpG, whose distribution is biased (Keshet et al 2006;Weber et al 2007). We suggest that the different T-DMR profiles observed in this study were due to the relatively low bias of HpyCH4IV.…”
Section: Correlations Between Expression Levels Of Genes and T-dmrs Imentioning
confidence: 99%
“…To identify genes with differentially methylated regions, several microarray technologies have been developed (Lieb et al 2006), and microarray technology has been applied to identify aberrantly methylated regions in cancer cells and characterize cell lines such as human embryonic stem cells (Hatada et al 2006;Keshet et al 2006;Ordway et al 2006;Rauch et al 2006;Shen et al 2006). However, the DNA methylation profiles obtained have not been directly related to gene function (Ching et al 2005;Eckhardt et al 2006;Khulan et al 2006).…”
mentioning
confidence: 99%
“…Initial studies using candidate gene approaches showed that many tumor suppressor genes undergo aberrant hypermethylation in cancer and that these events occur in a tumor type-specific manner (2,3). More recently, the use of genome-wide screening techniques has shown that hypermethylation in cancer occurs in different groups of genes, including those encoding transcription factors involved in tissue-specific differentiation and development (4). Various chromatin factors that are important in maintaining a normal silenced transcription status in a cell type-specific manner are now known to play a pivotal role in determining which genes become hypermethylated in cancer, when aberrantly used by the DNA methylation machinery.…”
Section: Introductionmentioning
confidence: 99%